Abundance and Distribution Patterns of Sea Urchins (Echinoidea) at Lakey Beach, Hu'u District, Dompu Regency - Fitriyani Fitriyani; Didik Santoso; Karnan Karnan (Jurnal Biologi Tropis, 2022)
Sea urchins are marine biota that have many benefits for life, so there is a need for information about the existence of sea urchins. The existence of sea urchins in marine ecosystems has a significant influence on the ecological balance, one of which is for coral reefs, because sea urchins are one of the control of macroalgae populations. The purpose of this study was to determine the species abundance, diversity index, dominance index and distribution pattern of sea urchins (Echinoidea) at Lakey Beach, Hu'u District, Dompu Regency. This type of research is descriptive exploratory using purposive sampling method (chosen method) in determining the three research stations. The data obtained were analyzed using the species formula, the Shanon Wienner diversity index, the Simpson dominance index, and the Morisita index. The results showed that the highest species on the Lakey Coast were Echinometra mathei with values of 0.60 Ind/mÃÂ² and Echinometra viridis with values of 0.45 Ind/mÃÂ². The diversity index of sea urchins at Lakey Beach is included in the moderate criteria with a species diversity index value of H'=1.03. The sea urchin dominance index in Lakey Beach is included in the low criteria with a species dominance index of 0.42. The distribution pattern of sea urchins on Lakey Beach includes two criteria, namely flocking and uniform. Types of sea urchins that belong to a grouped distribution pattern are Echinometra mathei and Echinometra viridis. While the types of sea urchins that have a uniform distribution pattern are Diadema setosum, Echinotrix calamaris (brown striped spines), Mespilia globulus, and Tripneustus gratilia. This research can be used as a reference and source of information to see the condition of the ecosystem in Lakey Beach, Hu'u District, Dompu Regency. So that the community and can preserve marine life such as sea urchins (Echinoidea) so that their lives can be maintained.